Comprehensive Analysis of Clinically Significant Hepatitis B Virus Mutations in Relation to Genotype, Subgenotype and Geographic Region - Araujo, Natalia M.; Teles, Sheila A.; Spitz, Natália (Frontiers in Microbiology, 2020)
Hepatitis B virus (HBV) is a highly variable DNA virus due to its unique life cycle, which involves an error-prone reverse transcriptase. The high substitution rate drives the evolution of HBV by generating genetic variants upon which selection operates. HBV mutants with clinical implications have been documented worldwide, indicating the potential for spreading and developing their own epidemiology. However, the prevalence of such mutants among the different HBV genotypes and subgenotypes has not been systematically analyzed. In the current study, we performed large-scale analysis of 6,479 full-length HBV genome sequences from genotypes A-H, with the aim of gaining comprehensive insights into the relationships of relevant mutations associated with immune escape, antiviral resistance and HCC development with HBV (sub)genotypes and geographic regions. Immune escape mutations were detected in 10.7% of the sequences, the most common being I/T126S (1.8%), G145R (1.2%), M133T (1.2%), and Q129R (1.0%). HBV genotype B showed the highest rate of escape mutations (14.7%) while genotype H had no mutations (P < 0.001). HCC-associated mutations were detected in 33.7% of the sequences, with significantly higher frequency of C1653T, T1753V and A1762T/G1764A in genotype G than C (P < 0.001). The overall frequencies of lamivudine-, telbivudine-, adefovir- and entecavir-resistant mutants were 7.3%, 7.2%, 0.5% and 0.2%, respectively, while only 0.05% showed reduced susceptibility to tenofovir. In particular, the highest frequency of lamivudine-resistant mutations was observed in genotype G and the lowest frequency in genotype E (32.5% and 0.3%; P < 0.001). The prevalence of HBV mutants was also biased by geographic location, with Northern America identified as one of the regions with the highest rates of immune escape, antiviral resistance, and HCC-associated mutants. The collective findings were discussed in light of natural selection and the known characteristics of HBV (sub)genotypes. Our data provide relevant information on the prevalence of clinically relevant HBV mutations, which may contribute to further improvement of diagnostic procedures, immunization programs, therapeutic protocols, and disease prognosis.